Pengaruh Model Blended Learning Tipe Flipped Classroom Terhadap Kemandirian Belajar Mahasiswa - Nur 'Azah; Sirojuddin Abror (Jayapangus Press, 2023)
The increasing role of information and communication technology in human life has an impact on the development of learning activities in educational institutions. Both lecturers and students are required to master and have insight regarding learning models that have been integrated with information and communication technology, one of the integrated models is the blended learning model. This study aims to determine the effect of the flipped classroom type blended learning model on the learning independence of Hasyim Asy'ari Tebuireng University students, Jombang. The research method uses a quantitative approach with a quasi-experimental research type (none equivalent control group design). The research subjects were 2 classes in semester 3 class of 2021 totaling 50 students, 2 class samples in the form of an experimental group, there were 25 children and a control group, there were 25 children. Collecting data using a Liket scale questionnaire related to learning independence. Data analysis used the normality test, then homogeneity test and hypothesis testing. The results of the study showed that there was a significant influence of the flipped classroom type model on the learning independence of Hasyim Asy'ari Tebuireng University students in Jombang significantly with the results of the independent sample t test value of 0.006.